Mental health of students in the upper level of a secondary school in Bangkok education service area office 1ะ A case study. - Uapongkitikul , N.; Suppapitiporn , S. (Chulalongkorn Medical Journal, 2023)
Objective : The purpose of this research was to study mental health and factors prevailing to the mental health of students เท the upper level of a secondary school เท Bangkok. Research design : A cross-sectional descriptive study. Participants : Upper level students of a secondary school in Bangkok. Methods : The subjects were 633 upper level students of a secondary school in Bangkok. The data were obtained through self -completed questionnaires including personal data, parent data, relationships within the family, the 10 items for evaluation of self-esteem questionnaires in Thai adapted from the Rosenberg self-esteem inventories and the 54-item mental health indicator questionnaire in Thai. The data were analyzed by SPSS for Windows. The utilized statistical tools consisted of percentage, mean, and standard deviation, chi-square and one-way ANOVA Results : The first grade of upper secondary school had 235 students (35.4%), Conclusion the second grade had 238 students (35.9%), and the third grade 3 had 190 students (28.7%). Three hundred and ninety-eight students were female (60%) and 265 were male (40%). The Thai mental health indicator scores indicated that 48.1% of the subjects had fair mental health, 33.3% had good mental health, and 18.6% had poor mental health; 84.8% of the subjects had high self-esteem.The factors related mental health were education level, number of sibling, playing music, health, grief event, mental health problems, attitude toward smoking, family relationships and student self-esteem. Conclusion : The majority of upper secondary students had fair mental health. Keywords However about one-fifth of the subjects had poor mental health. This should be further evaluated and followed up. Mental health and related factors should be concerned. The poor mental health students should be cared for and reassured for better mental health. The results of this research could be utilized as a guideline for administrators to manage cooperation between schools and parents as well as a promotion of good mental health for students. This promotion should be concerned as immunity to the current continuously changing environment.